LOCAL METHODS FOR DETECTING AND PREVENTING NERVE DAMAGE IN PRESCHOOL CHILDREN - Hujanazarova Nargiza Mirzamahmudovna; Ilxomjonova Xusnora Iqboljon qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In the socialization of preschool children, it is very important that they are healthy from a physiological point of view. After all, physiologically healthy children have a positive attitude towards the environment, social subjects, and otherwise their attitude becomes negative. The positive or negative attitude of children to their natural and social environment is associated with nervous disorders that they experience. The article discusses these phenomena and international methods of their elimination.